Ghost town at sundown - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1997)
Their magic tree house takes Jack and Annie back to the Wild West, where they experience excitement and danger and try to solve a riddle.
"A stepping stone book."
RL: 2.4
006-009
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; West (U.S.) -- Fiction